2021
DOI: 10.1002/clc.23599
|View full text |Cite
|
Sign up to set email alerts
|

Percutaneous edge‐to‐edge repair of severe mitral regurgitation using the MitraClip XTR versus NTR system

Abstract: Background Transcatheter mitral valve repair (TMVR) has shown to improve symptoms and functional capacity in patients with severe mitral valve regurgitation (MR). Novel device developments provide the technology to treat patients with complex anatomies and large coaptation gaps. Nevertheless, the question of superiority of one device remains unanswered. We aimed to compare the MitraClip XTR and MitraClip NTR system in a real world setting. Hypothesis TMVR with the MitraClip XTR system is equally effective, but… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
21
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 12 publications
(23 citation statements)
references
References 27 publications
1
21
1
Order By: Relevance
“…Of relevance for the application of different clip sizes could be the reported association of usage of a larger device with more SLDAs and leaflet tears. 9 Leaflet adverse events within EXPAND have been further analysed by an expert panel. 10 Reassuringly, only two peri-procedural SLDA were reported, with further six SLDA through 30 days and no other leaflet related adverse events through 1 year.…”
Section: Patients Treated With Ntr Versus Xtr Devicementioning
confidence: 99%
See 2 more Smart Citations
“…Of relevance for the application of different clip sizes could be the reported association of usage of a larger device with more SLDAs and leaflet tears. 9 Leaflet adverse events within EXPAND have been further analysed by an expert panel. 10 Reassuringly, only two peri-procedural SLDA were reported, with further six SLDA through 30 days and no other leaflet related adverse events through 1 year.…”
Section: Patients Treated With Ntr Versus Xtr Devicementioning
confidence: 99%
“…This 1.9% rate of SLDA is lower than the very early experience with different MitraClip devices reported before. 9,17 This could be due to the aetiology of SMR. In SMR, the prevalence of fragile and degenerative leaflets or extensive mitral annulus calcifications should be low.…”
Section: Patients Treated With Ntr Versus Xtr Devicementioning
confidence: 99%
See 1 more Smart Citation
“…3 Patients with thinner mitral valve (MV) leaflets (such as in functional, secondary MR) and patients with more fragile tissue would be at higher risk of leaflet injury. The third-generation XTR system carries higher rates of leaflet injury than the original NT MitraClip (Abbott) 3 due to its larger size (12 vs 9 mm cases-anesthesia-analgesia.org 3 clip arm length) and greater number of frictional elements (6 vs 4), causing increased leaflet stress. 3,4 Incidence of leaflet damage with the fourth-generation devices which allow for independent leaflet grasping has yet to be thoroughly studied.…”
Section: Discussionmentioning
confidence: 99%
“…When planning TV TEER procedures, the choice of device can present a challenge given that these devices were developed for the mitral valve, whereas tricuspid valve leaflets are thinner and more fragile and severe TR tends to involve larger leaflet malcoaptation gaps. Some evidence from MV TEER has shown that the XTR clip leads to more SLDA and leaflet tearing ( 57 ), however the length of the XTR device is theoretically ideal when treating severe TR as most patients have malcoaptation gaps. The use of MitraClip XTR vs. NTR devices has been shown to achieve a higher procedural success rate (TR ≤ 2+ 80% vs. 70%), was able to treat TR with larger coaptation defects including those with torrential TR and lead to a greater reduction in TR.…”
Section: Device Selection For Combined Teermentioning
confidence: 99%